2016
DOI: 10.1002/ecs2.1592
|View full text |Cite
|
Sign up to set email alerts
|

Changes in community phylogenetic structure in a North American forest chronosequence

Abstract: Citation: Pastore, A. I., and B. P. Scherer. 2016. Changes in community phylogenetic structure in a North American forest chronosequence. Ecosphere 7(12):e01592. 10.1002/ecs2.1592Abstract. Several studies of succession in tropical and subtropical climates include phylogenetic analyses of the plant communities; the majority of these studies find a shift from more closely related to less closely related assemblages over succession. It has been suggested that this pattern indicates a shift from abiotic to biotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This prediction was consistent with that of Mayfield and Levine (). Actual field studies, however, have often found shifts from more closely related (functionally similar) to less closely related (dissimilar) species assemblages during succession (Letcher, ; Li, Cadotte, Meiners, Hua, Jiang, et al, ; Shooner et al, ; Pastore & Scherer, ; reviewed in Meiners et al, ). There are several potential explanations for this discrepancy between the prediction and observations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This prediction was consistent with that of Mayfield and Levine (). Actual field studies, however, have often found shifts from more closely related (functionally similar) to less closely related (dissimilar) species assemblages during succession (Letcher, ; Li, Cadotte, Meiners, Hua, Jiang, et al, ; Shooner et al, ; Pastore & Scherer, ; reviewed in Meiners et al, ). There are several potential explanations for this discrepancy between the prediction and observations.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential explanations for this discrepancy between the prediction and observations. One possibility is that the systems had not reached a competitive equilibrium at the time of the aforementioned studies (Letcher, 2010;Li, Cadotte, Meiners, Hua, Jiang, et al, 2015;Pastore & Scherer, 2016;Shooner et al, 2015). For example, despite their analysis of 50 years of successional data, Li, Cadotte, Meiners, Hua, Jiang, et al (2015) found that their plots transitioned from meadows to early secondary forests, and this ecosystem would likely require many more decades to truly reach equilibrium (however, note that this limitation was reasonable because their main focus was on understanding the change in community patterns during succession, not the equilibrium pattern per se).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reason is that dominant plant species are replaced during the plant succession and therefore soil organisms may be influenced by changes in plant communities caused by succession because plants can provide the basic resources for the soil food web (i.e., rhizodeposits, shoot and root litter; Bardgett & Wardle, 2010; Coleman et al, 2004). However, most previous studies on the succession have focused on the aboveground community responses (Liu et al, 2019; Pastore & Scherer, 2016; Teixeira et al, 2020), with less attention to belowground community (Gundale & Kardol, 2021; Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%